Protective antibodies against human parainfluenza virus type 3 infection. Issue 1 (1st January 2021) - Boonyaratanakornkit, Jim; Singh, Suruchi; Weidle, Connor; Rodarte, Justas; Bakthavatsalam, Ramasamy; Perkins, Jonathan; Stewart-Jones, Guillaume B.E.; Kwong, Peter D.; McGuire, Andrew T.; Pancera, Marie; Taylor, Justin J.
ABSTRACT: Human parainfluenza virus type III (HPIV3) is a common respiratory pathogen that afflicts children and can be fatal in vulnerable populations, including the immunocompromised. There are currently no effective vaccines or therapeutics available, resulting in tens of thousands of hospitalizations per year. In an effort to discover a protective antibody against HPIV3, we screened the B cell repertoires from peripheral blood, tonsils, and spleen from healthy children and adults. These analyses yielded five monoclonal antibodies that potently neutralized HPIV3 in vitro . These HPIV3-neutralizing antibodies targeted two non-overlapping epitopes of the HPIV3 F protein, with most targeting the apex. Prophylactic administration of one of these antibodies, PI3-E12, resulted in potent protection against HPIV3 infection in cotton rats. Additionally, PI3-E12 could also be used therapeutically to suppress HPIV3 in immunocompromised animals. These results demonstrate the potential clinical utility of PI3-E12 for the prevention or treatment of HPIV3 in both immunocompetent and immunocompromised individuals.